IMPLEMENTASI METODE SYARH HADIS PADA HADIS-HADIS TENTANG ISLAM, IMAN DAN IHSAN - Siregar, Muhammad Nuh (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
In the general public, there is still debate about the understanding between Islam and faith, whether it is different or the same. Likewise, which one is first in a person, is Islam new faith or faith first then Islam? In answering this question, of course, a comprehensive study from various points of view is necessary. This paper will examine in detail from the point of view of specific Hadith studies. In the Hadith study specifically, this discussion is found in several narrations which are popularly known as the Hadith "Jibril". Editors of this Hadith "Jibril" in the history of al-Bukhari and Muslim, the order of questions raised by Jibril to the Prophet Muhammad is different. In the first narrative the first order asked by Jibril is what is Islam, while in the second narration the question that is asked is what is faith? Al-Muzanni and al-Bagawi commented on Gabriel's question and Rasulullah made the word Islam here as "every visible action and faith as the name for the belief hidden in the heart." This does not mean that the act is not part of faith and does not mean that justification of the heart is not part of Islam, but as an explanation that everything is one and the combination of the two is called religion. "Abu 'Amr bin as-Salah said that; based on what we have mentioned and proven, there is an understanding that faith and Islam can be combined and separated. Every believer is a Muslim, but not every Muslim is a believer. When it is mentioned Islam and faith together, the meaning is different, but if it is mentioned separately, the meaning is the same. The point is that if it is said to be Islam only then it is joined to faith and vice versa when it is mentioned only faith then it is joined there. But if you say both, the meaning is different. When it says Islam and faith, it means Islam from the outward point of view while faith is from the inner side.